A Tool to Build a Working-Class Environmental Movement: Proposal for an Industrial Workers Safety Act - Clara R. Goodwin (Washington University Journal of Law and Policy, 2023)
The consequences of climate change are far-reaching and ripple throughout various aspects of society; one such consequence is the urgent need for overhaul of systems across the energy production, transportation, and industrial manufacturing industries. Unfortunately, such system improvements run contrary to the interests of powerful, influential capital sectors, thus, needed reform will likely require a mass social movement amongst the working class. This Note seeks highlight the ways in which the mainstream environmental movement has positioned itself as separate from, and potentially antagonistic to, an industrial working class whose livelihood is tied to the production of consumer goods. However, the environmental justice movement has begun the critical work toward reform. This Note suggests that in order to successfully collaborate toward a more sustainable future, the environmental and labor movements need to deal not only with the economic effects associated with transition but also with the tangible health and environmental effects of unsafe labor practices and industrial pollution. The Author argues that this will require statutory protections because the current scheme is lacking; while the Occupational Safety and Health Act and federal environmental laws establish safety and pollution standards, the enforcement efforts are almost absent. This Note proposes an Industrial Workers Safety Act which would include a private right of action to sue for enforcement of safety standards, a procedural right to agency review of safety and environment violations, whistleblower protections, and a statutory definition of harm for purposes of federal environmental law.
Keywords: Climate Change; Environment; Labor; Pollution; Working Class